Teacher Competence in Improving Student Achievement - Jihan; Annisa Nurfadillah; Taufik Hidayat Daulay (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
His study describes teacher competence in improving student achievement. In this paper, the author uses a qualitative descriptive research method. Data collection techniques by taking from various sources both from books, journals and other relevant sources. The results obtained in this study indicate that teacher competence has a major influence on improving student achievement. The teacher competencies include; (1) Paedagogical Competence, (2) Personal Competence, (3) Social Competence, (4) Professional Competence. Therefore, teacher competence is very necessary as a support for achieving good and useful student achievement.